Effect of Nano-Fertilizers on Growth and Yield of Summer Hybrid Maize (Zea mays L.) in Gangetic Plains of India - Roy, Deblina; Sengupta, Kajal; Mondal, Ramyajit; Gunri, Sunil Kumar; Ali, Osman; Madhu, H. S. (International Journal of Bio-resource and Stress Management, 2023)
Nano fertilizer contains the nutrients in a concentrated and energy farm which would also pave the way to have a successful harvest without soil application and to reduce the ill effect on soil. In this regard, the present experiment was carried out over two years at BCKV, West Bengal, India in the Gangetic alluvial soil, to assess the impact of nano fertilizer management on growth and yield of summer hybrid maize cv. ‘Kaveri 50’. The treatments comprised different percentage of recommended dose of fertilizer (RDF) with or without nano fertilizer application. Results revealed that application of 50 % RDZn and 100 % N-P-K along with 2 foliar sprays of Nano-Zn @ 4 ml litre-1 at 25 and 50 DAS (T8) recorded better results of growth attributes. The yield attributes like number of cobs plant-1 (1.30), cob length (21.30 cm), cob girth (16.25 cm), number of rows cob-1 (13.97), number of grains cob-1 (317.6), seed index (25.40 g) and single cob weight (128.74 g) also found highest from the same treatment. Higher grain (8.16 t ha-1) and stover yield (12.22 t ha-1) were recorded in T8 treatment and yield variation was 2.21 to 63.86 % over control with highest benefit-cost ratio (2.35). Hence, application of 50 % RDZn and 100 % N-P-K along with 2 foliar sprays of Nano-Zn @ 4 ml litre-1 at 25 and 50 DAS could be more effective in augmenting yield, available nutrient status and economics of summer maize in the Gangetic plains of India.